Peer assessment experiences in the lower primary ESL classrooms in Malaysia: Teachers' perspectives - Ma'arop, Amrien Hamila; Abd Samad, Arshad (Horizon Research Publishing, 2020)
Peer assessment is increasingly being emphasized as part of formative assessment due to its rich nature in developing independent and autonomous learners. However, in Malaysia, the practice of peer assessment is still limited. While past studies have indicated that conceptions predict classroom practices, and studying teachers’ conception on peer assessment are important especially now that the transformation of assessment practice is a major item in the national educational agenda. Hence, this study aims to explore peer assessment experiences in the lower primary ESL classroom among teachers in the state of Selangor. The study adopted the qualitative research method, with three primary ESL teachers who were purposefully selected as the participants of the study. Data were collected through in-depth interviews and were analyzed for emerging themes. The findings revealed that participating teachers in this study viewed peer assessment as an interpersonal, intrapersonal and active, cognitive process. In implementing peer assessment, teachers generally engaged in several processes before and while implementing the activity. In the planning stage, the teachers decided on the activity and strategy, presented success criteria and specified feedback forms to be used by the students and while during the activity, teacher oriented the task clearly and facilitated the process through monitoring. This study contributed to a better understanding of teachers’ perspectives on implementing peer assessment in the lower primary ESL classrooms in Malaysia.